Richard Wagner’s prose sketches for Jesus of Nazareth: historical and theological reflections on an uncompleted opera - Bell, Richard H. (Brill, 2017)
In May 1849 Wagner fled Dresden after the failure of the uprising of which he was a leader. His last creative work in Dresden was prose sketches for an opera Jesus of Nazareth, the result of his study of the Graeco-Roman world and the New Testament together with some knowledge of biblical criticism. Although he portrays Jesus as a social revolutionary in that he attacks the Pharisees, oppression and injustice, he is by no means a political messiah; indeed Wagner emphases his sacrificial death which results in the giving of the Holy Spirit. Key theological themes of the work which I explore include Jesus’ messiahship, law and freedom, and the significance of his death.